R-Loop Formation In Trans at an AGGAG Repeat - Toriumi, Kazuya; Tsukahara, Takuma; Hanai, Ryo (Journal of Nucleic Acids, 2013)
Formation of RNA-DNA hybrid, or R-loop, was studied in vitro by transcribing an AGGAG repeat with T7 RNA polymerase. When ribonuclease T1 was present, R-loop formation in cis was diminished, indicating that the transcript was separated from the template and reassociated with it. The transcript was found to form an R-loop in trans with DNA comprising the AGGAG repeat, when the DNA was supercoiled. Results of chemical modification indicated that the duplex opened at the AGGAG repeat under negative supercoiling.